The Impact of Intercultural Perspectives on Environmental Ethics - Molotokienė Ernesta (E3S Web of Conferences)
Intercultural environmental ethics is one of the most recent research projects to analyze a wide range of ethical issues arising from the multidisciplinary perspective of societies and cultures. Intercultural environmental ethics seeks to identify the existing different cultural, value beliefs, to define universal environmental ethical principles. Different cultures disagree on common universal moral decisions because they are based on unique worldviews and value systems, and there is no universally accepted epistemically sound way to resolve such moral disagreements. The question is, what are the basic assumptions underpinning the impact of intercultural ethics that would enable the common development and application of a system of universal environmental ethical principles in different regions and cultures of the world? The article hypothesizes that a synthesis of classical Aristotelian virtue ethics, Confucian ethics, and African ubuntu philosophical ethics could underpin intercultural ethics, embodying the universal environmental ethical values of Western and Eastern cultures in intercultural environmental ethics theory.